1979
DOI: 10.1111/j.1445-5994.1979.tb04148.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐existing Coeliac and Inflammatory Bowel Disease in a Patient with Turner's Syndrome

Abstract: A patient, aged 20, with Turner's syndrome was found to have both coeliac disease and chronic ulcerative colitis. Although a gluten-free diet restored to normal the jejunal biopsy, persisting diarrhoea was found to be due to coexisting left-sided ulcerative colitis. A search of the literature revealed only three detailed reports of chronic inflammatory bowel disease in coeliac patients, one of coeliac disease in Turner's syndrome and three of inflammatory bowel disease in Turner's syndrome. Growth failure with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…MÉTHODES : On a fait subir un test de dépistage de la MC à quarantecinq fillettes atteintes du ST de façon prospective au moyen d'épreuves à l'insu par test standard : l'anticorps endomysial (EmA) dirigé contre l'imvoir page suivante A n association between Turner syndrome (TS) and celiac disease (CD) has been suggested in several case reports (1)(2)(3)(4). More recently, studies from Italy and Sweden showed that the prevalence of biopsy-proven CD among girls with TS is 5% to 9% (5)(6)(7). This study aimed to ascertain the prevalence of CD in the girls with TS followed at British Columbia's Children's Hospital, University of British Columbia (UBC), Vancouver, British Columbia.…”
mentioning
confidence: 99%
“…MÉTHODES : On a fait subir un test de dépistage de la MC à quarantecinq fillettes atteintes du ST de façon prospective au moyen d'épreuves à l'insu par test standard : l'anticorps endomysial (EmA) dirigé contre l'imvoir page suivante A n association between Turner syndrome (TS) and celiac disease (CD) has been suggested in several case reports (1)(2)(3)(4). More recently, studies from Italy and Sweden showed that the prevalence of biopsy-proven CD among girls with TS is 5% to 9% (5)(6)(7). This study aimed to ascertain the prevalence of CD in the girls with TS followed at British Columbia's Children's Hospital, University of British Columbia (UBC), Vancouver, British Columbia.…”
mentioning
confidence: 99%
“…Thus, it remains uncertain whether our patient had a chance association of CD and atypical TS. It seems remarkable, however, that among the 10 cases with this association in the literature (1‐5 and this case), a total of 4 were reported to have IgA deficiency (2 and this case). Therefore, and although this is also the result of a retrospective analysis of available data, the association of CD and TS may have been overlooked in the past, particularly in monosymptomatic girls with growth failure.…”
mentioning
confidence: 66%
“…Nine cases (34%) were associated to other comorbidities such as autoimmune diseases (Hashimoto thyroiditis, primary biliary cirrhosis, acquired von Willebrand disease, celiac disease, and primary sclerosing cholangitis) and cardiac defects [bicuspid aortic valve, coarctation of the aorta, and atrial septal defect) ( 13 , 17 , 21 , 24 , 26 , 27 , 29 , 33 ). Treatment with biologic drugs (infliximab, adalimumab, and ustekinumab) was reported in two cases, and in one case, a drug-induced cardiomyopathy during treatment with adalimumab was described ( 29 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…The karyotype of the included cases was characterized by the absence of an X chromosome (monosomy or mosaic monosomy) in 12 cases ( 12 , 14 16 , 18 , 21 , 24 , 26 , 27 , 29 ) or by the presence of a structurally abnormal X chromosome (or mosaic pattern with structurally abnormal X chromosome) in the remaining 13 cases ( 10 , 11 , 13 17 , 19 , 20 , 28 ). In one case, the karyotype was not specified ( 33 ).…”
Section: Resultsmentioning
confidence: 99%